ANALYSIS OF FACTORS RELATED TO OCCUPATIONAL STRESS ON HEALTH WORKERS DURING THE COVID-19 PANDEMIC (LITERATURE REVIEW) - Ayunda Larasati Sekarputri; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
The COVID-19 pandemic that continues to this day puts great pressure on health workers as the front line in handling COVID-19. The great pressure experienced by health workers can cause mental health problems for health workers, such as stress, anxiety, symptoms of depression, insomnia, anger, and fear. This research is a literature review. The literature used in this study uses 4 electronic databases, namely Google Scholar, Science Direct, PubMed, and ProQuest, with the keywords